SOCIALIZATION “ARCA” AS AN INTRODUCING HISTORICAL TOURISM MALANG REGENCY - Noveria Anggraeni Fiaji; Prima Zulvarina; Khalid Rahman; In’amul Wafi; Zenitha Kurnia Putri (UPT. PKM UB, 2022)
The service team targeted the Malang Regency Tourism and Culture Office as the organizer of activities in the tourism sector. The main task of the Department of Tourism and Culture is tourism promotion. Therefore, it is hoped that the ARCA application can be part of a tourism promotion strategy in Malang Regency. Candi Jago is chosen as the object of this application because on the main terrace of the temple there are Reliefs about fables that contain moral values for tourists. With the ARCA Application, tourists do not need to hesitate anymore to be able to visit Candi Jago because ARCA can help tourists to read the Reliefs found on the main terrace with 3-Dimensional AR (Augmented Reality) media in the form of animated videos. The methods used are the online lecture method, the online question and answer method, and the online demonstration method. The results of the evaluation of the outreach, the ARCA application is still limited and available on the Play Store and cannot be downloaded on the App Store, because during the application trial, there were participants who asked why on their smartphone they could not download the application. Meanwhile, another obstacle is that your smartphone does not support being able to download the ARCA application because it requires an upgrade to the latest version.